Rethinking the strongest link: VAL, ratings, and team success in Hungarian basketball - Nagy, Benedek Ágost; Nagy, Botond Ágoston; Nagy, Ágoston; Gáll, József; Sterbenz, Tamás (Frontiers in Sports and Active Living, 2025)
IntroductionThis study evaluates the impact of individual player performance–particularly the VAL rating–on team success in professional basketball. It examines whether basketball operates as a “strong-link” sport, where outcomes depend primarily on top-performing players.MethodsA quantitative analysis was conducted on the 2022/2023 Hungarian NB I/A men's league, using 21 offensive and defensive statistical indicators. Data were collected from official league sources and analyzed using IBM SPSS Statistics version 28.0.ResultsOur findings reveal no significant correlation between individual VAL rankings and team standings. However, offensive and defensive ratings, as well as NET ratings (points scored over opponents per 100 possessions), were strongly associated with team performance, especially among foreign and young players. The VAL metric was more influenced by offensive than defensive performance. Limited playing time and experience may have affected the performance metrics of young players.DiscussionThese results suggest that while basketball reflects strong-link sport characteristics, traditional metrics like VAL may not fully capture a player's contribution to team success. A more comprehensive approach-incorporating both offensive and defensive indicators-could offer a clearer evaluation of player impact. Future research should also explore psychological, tactical, and social factors to better understand individual roles in team performance.